2019
DOI: 10.1111/1471-0307.12597
|View full text |Cite
|
Sign up to set email alerts
|

‘Lipase and protease production of dairy Penicillium sp. on milk‐protein‐based solid substrates’

Abstract: The lipolytic and proteolytic activity of Penicillium camemberti PC TT033 and Penicillium roqueforti PR G3, cultured on the whey solids or simulated cheese media, were compared under several pH reaction conditions. Lipolytic activity was higher when both strains had been cultured on the whey medium than on the simulated cheese medium, whereas proteolytic activity was less influenced by the culture medium. The relationship between the reaction pH and these enzyme activities was dependent on the culture medium, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…These cheeses are coated with a white mycelium produced by Penicillium camemberti , which is responsible for chemical reactions that occur during growth and ripening (Kumura et al . ). These reactions are responsible for the typical appearance, taste and aroma characteristics of the cheese (Spinnler and Gripon ).…”
Section: Introductionmentioning
confidence: 97%
“…These cheeses are coated with a white mycelium produced by Penicillium camemberti , which is responsible for chemical reactions that occur during growth and ripening (Kumura et al . ). These reactions are responsible for the typical appearance, taste and aroma characteristics of the cheese (Spinnler and Gripon ).…”
Section: Introductionmentioning
confidence: 97%
“…The Ap/Pe enterotype exhibited elevated genes related to sphingolipid metabolism, indicating a potential emphasis on the synthesis and degradation of sphingolipids, crucial components of cell membranes and important in cell signaling processes. Other studies also reported that Aspergillus and Penicillium produced a diverse range of hydrolytic enzymes such as lipase and protease 48 , 49 . The breakdown of lipid or protein complexes by these enzymes facilitates their enhanced absorption by the host, potentially influencing body composition from fat and protein consumption.…”
Section: Discussionmentioning
confidence: 93%
“…Aspergillus species, such as Aspergillus flavus and Aspergillus niger, are renowned producers of mycotoxins, secondary metabolites that pose significant health risks when present in contaminated food [61][62][63]. Similarly, Penicillium species, such as Penicillium roqueforti and Penicillium camemberti, play pivotal roles in the production of various fermented food, including blue cheese and Camembert, where they contribute to flavor development and texture modification through their enzymatic activities [64,65]. In addition to filamentous molds, yeasts constitute another prominent component of the fungal communities inhabiting food products.…”
Section: Fungal Diversity and Identification In Foodmentioning
confidence: 99%